On the malleability of fairness ideals: Order effects in partial and impartial allocation tasks - Kathrin Dengler-Roscher; Natalia Montinari; Marian Panganiban; Matteo Ploner; Benedikt Werner (Friedrich Schiller University Jena, 2015)
How malleable are peoples fairness ideals? Although fairness is an oft-invoked concept in allocation situations, it is still unclear whether and to what extent peoples allocations reflect their fairness ideals. We investigate in a laboratory experiment whether peoples fairness ideals vary with respect to changes in the order in which they undertake two allocation tasks. Participants first generate resources in a real-effort task and then distribute them. In the partial allocation task, the participant determines the earnings for himself and another participant. In the impartial allocation task, the participant determines the earnings for two other participants. We also manipulate the participants experience, i.e, whether they took part in similar allocation experiments before. We find that participants are more likely to allocate more resources to themselves than what they earned in the real-effort task when they decide partially. Exclusively for inexperienced participants, deciding impartially first dampens selfish behavior when they decide partially.
Keywords: C72; C91; D63; D64; 330; dictator; fairness; fairness bias; impartial spectators; partial stakeholders; proportionality principle